Gambaran Pengetahuan Masyarakat Tentang Pentingnya Konsumsi Vitamin Selama Masa Pandemi Covid-19 Di Dusun Salulayang - Jesika Turuallo; Askur; Wita Oileri Tikirik (Yayasan Literasi Sains Indonesia, 2022)
Boosting your immune system is one of the keys to preventing the spread of the Covid-19 virus. Consuming a balanced nutritious diet is one way to keep the immune system primed. However, we also need to increase the consumption of foods that contain nutrients that play an active role in increasing endurance, including vitamins A, C, E, B and D3. This study aims to determine public knowledge about the importance of consuming vitamins during the Covid-19 pandemic Salulayang Hamlet. The type of research used is descriptive with a quantitative approach, using a questionnaire instrument conducted in October-November 2021 with a population of 613 people with a sampling formula using the Slovin formula and a sample of 86 people. Based on the results of the study, it was found that the level of good knowledge was 73.3% while those who had poor knowledge were 26.7%. So it can be concluded that the knowledge of the people of Salulayang Hamlet about the importance of consuming vitamins during the Covid-19 pandemic can be categorized as good. The types of vitamins consumed by the people of Dusun Salulayang are vitamin C, vitamin B complex, and vitamin D. The most consumed vitamin is vitamin C.